2016
DOI: 10.1242/dev.128074
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs: analysis, expression and potential functions

Abstract: Just a few years ago, it had been assumed that the dominant RNA isoforms produced from eukaryotic genes were variants of messenger RNA, functioning as intermediates in gene expression. In early 2012, however, a surprising discovery was made: circular RNA (circRNA) was shown to be a transcriptional product in thousands of human and mouse genes and in hundreds of cases constituted the dominant RNA isoform. Subsequent studies revealed that the expression of circRNAs is developmentally regulated, tissue and cell-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
617
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 739 publications
(624 citation statements)
references
References 67 publications
(131 reference statements)
3
617
1
3
Order By: Relevance
“…Current biochemical methods are mainly aimed at proving the circularity of putative circRNAs and include RT-PCR followed by inverse PCR, Northern Blotting with probes designed to target the circularised junction sequences, and RNaseR sensitivity tests 25 . Another validation method takes advantage of the high processivity and strand displacement capabilities of reverse transcriptases which can yield cDNAs consisting of concatemers of circRNAs, a phenomenon known as rolling-circle RT.…”
Section: /17mentioning
confidence: 99%
“…Current biochemical methods are mainly aimed at proving the circularity of putative circRNAs and include RT-PCR followed by inverse PCR, Northern Blotting with probes designed to target the circularised junction sequences, and RNaseR sensitivity tests 25 . Another validation method takes advantage of the high processivity and strand displacement capabilities of reverse transcriptases which can yield cDNAs consisting of concatemers of circRNAs, a phenomenon known as rolling-circle RT.…”
Section: /17mentioning
confidence: 99%
“…In particular, thousands of circular RNAs with little or no protein-coding capacity are generated from genes in a variety of eukaryotes, including humans, mice, C. elegans, D. melanogaster, S. pombe, and plants (For a review see refs. [6][7][8][9][10][11][12] ). Some of these circular RNAs are expressed at much higher levels than their associated linear mRNAs, 13,14 suggesting that the main function of some protein-coding genes may be to produce circular noncoding RNAs rather than proteins.…”
Section: Introductionmentioning
confidence: 99%
“…However, authors of an earlier study observed and sequenced the rolling RT products of circRNA in cDNA [8]. This phenomenon, known as rolling-circle RT, can lead to a laddering effect on a gel after PCR but can also result in an overestimation of circRNA by qPCR [18].…”
Section: Introductionmentioning
confidence: 99%